2013
DOI: 10.1007/978-3-642-37374-9_75
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Information Quality of e-Learning Systems in KSA: Attitudes and Perceptions of Learners

Abstract: Abstract. The introduction of e-learning, with the easy availability of course materials and related resources, has had a major impact on students and lecturers in higher education. However, few studies have been conducted to measure the information quality of e-learning on educational institutions in Saudi Arabia. This paper looks at the issues of using e-learning systems and the effect on higher education institutions in the Kingdom of Saudi Arabia (KSA). The findings of this study show positive attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Previous literature is also consistent with the current study and provides evidence that e-information quality has a positive role to enhance students e-learning. As previous studies investigated a significant positive effect of e-information on student learning (Alkhalaf et al, 2013;Mammo and gulube, 2019). Nevertheless, WOM also have a major role in universities during COVID-19.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous literature is also consistent with the current study and provides evidence that e-information quality has a positive role to enhance students e-learning. As previous studies investigated a significant positive effect of e-information on student learning (Alkhalaf et al, 2013;Mammo and gulube, 2019). Nevertheless, WOM also have a major role in universities during COVID-19.…”
Section: Discussionmentioning
confidence: 85%
“…The empirical studies have proved that the higher the quality of e-information provided, the better is the e-learning of students. The comparison between typical services and web-based services has given a base for the perception that all the features of service quality do not influence the whole service quality given to the students to the same degree (Alkhalaf et al, 2013). In this tough situation of coronavirus, there is an extensive level of need about the high quality of e-information that enhances the e-learning of the students.…”
Section: E-information Quality On E-learning Of Studentsmentioning
confidence: 99%
“…Electronic information had a major, positive impact on student learning as investigated in previous studies (Mammo & Ngulube, 2019). Services provided form the basis for the perception that all service quality characteristics do not affect the overall quality of service provided to students (Alkhalaf et. al., 2013).…”
Section: Information Qualitymentioning
confidence: 90%
“…(2013) (36) who revealed that more than forty percent of student confirmed that an e-learning system provides information in an easy, simple, clear, and wellcoordinated way.…”
Section: Information Qualitymentioning
confidence: 99%